Vision, Voice and Validation for women’s collectives in community decision making processes (VVV tool): A tool in the CGIAR Gender Transformative Research Methodologies (GTRM) toolkit - Singh, Sonali; Shijagurumayum, Meghajit (2025)
Tool 6 in the Gender Transformative Research Methodologies Toolkit. VVV works to strengthen the voice of women and of other socially marginalized people in community level decision-making processes. To do this VVV provides tools which facilitate women and other socially marginalized people to build confidence and develop collective agency. This enables them to participate more effectively in community decision-making thereby supporting the inclusivity and accountability of institutions. Focus on individuals and organizations.